2017
DOI: 10.1111/jcmm.13117
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of endothelial prolyl hydroxylase domain protein‐2 promotes renal vascular remodelling and fibrosis in mice

Abstract: Accumulating evidence demonstrates that hypoxia‐inducible factor (HIF‐α) hydroxylase system has a critical role in vascular remodelling. Using an endothelial‐specific prolyl hydroxylase domain protein‐2 (PHD2) knockout (PHD2ECKO) mouse model, this study investigates the regulatory role of endothelial HIF‐α hydroxylase system in the development of renal fibrosis. Knockout of PHD2 in EC up‐regulated the expression of HIF‐1α and HIF‐2α, resulting in a significant decline of renal function as evidenced by elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…We found that the expression of TGF-β was significantly increased in the PHD2 EC KO mice. Our previous studies have provided evidence that activation of TGF-β signaling pathway may contribute to pericyte differentiation into myofibroblasts and fibrosis in the PHD2 EC KO mice [21,22]. Therefore, increased Ang-2 and TGF-β in the liver tissues may be responsible for hepatic fibrosis in the PHD2 EC KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the expression of TGF-β was significantly increased in the PHD2 EC KO mice. Our previous studies have provided evidence that activation of TGF-β signaling pathway may contribute to pericyte differentiation into myofibroblasts and fibrosis in the PHD2 EC KO mice [21,22]. Therefore, increased Ang-2 and TGF-β in the liver tissues may be responsible for hepatic fibrosis in the PHD2 EC KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…In three PHD isoforms, PHD2 is considered as the most important HIF-α-regulating isoform [18][19][20]. Our recent studies indicate the expression of PHD2 in endothelial cells has a critical role in the regulation of vascular remodeling and the development of fibrosis by the mechanism involving in upregulation of HIF-2α expression in lung and kidney [21,22]. Accumulating evidence suggests some of hypoxia-associated genes were not regulated by HIFs, implicating potential HIF-independent pathways that are controlled by prolyl hydroxylase domain (PHD) enzymes [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar synergistic interaction of HIF and TGF-β1/SMAD3 signalling has also been reported in the regulation of VEGF, endothelin and erythropoietin expression [ 24 ]. Furthermore, accumulation of HIF in the endothelial cells of endothelial specific propyl hydroxylase-2 knockout mice upregulated TGF-β1 expression, resulting in significantly poorer renal function [ 30 ]. In a study using a renal tubular cell line in which transcription of HIF-α was absent, there was a decrease in basal and TGF-β1 stimulated Col-1 expression [ 31 ].…”
Section: Role Of Hypoxia and Hypoxia-inducible Factor (Hif)mentioning
confidence: 99%
“…Although it is evident that PHD deficiency is involved in tissue fibrosis (chapter 2, 6), not much is known about the direct consequence of PHD inhibition in fibroblast-like cells, or how paracrine signaling of PHD deficient cells can change fibroblast behavior. Corroboration of our paracrine signaling model (chapter 6) was given by Wang and colleagues, showing increased pericyte coverage of small blood vessels in kidney and lung tissue of endothelial cell PHD2ko mice [155][156][157]. In addition, pulmonary blood vessel adventitia was enriched with fibroblast-like cells in endothelial cell PHD2ko mice [158].…”
Section: The Increasing Understanding Of Mesenchymal Cell Biology: a mentioning
confidence: 52%